Simulations in Medicine Computer-aided diagnostics and therapy - Roterman-Konieczna, Irena (De Gruyter, 2020)
Modern practical medicine requires high tech in diagnostics and therapy and in consequence in education. All disciplines use computers to handle large data bases allowing individual therapy, to interpret large data bases in form of neuronal signals, help visualization of organs during surgery. This book contains chapters on personalised therapy, advanced diagnostics in neurology, modern techniques like robotic surgery (da Vinci robots), 3D-printing and 3D-bioprinting, augmented reality applied in medical diagnostics and therapy. It is impossible without fast large scale data mining in both: clinical data interpretation as well as in hospital organization including hybrid surgery rooms and personal data flow. The book is based on a course for medical students organized in the editor's department. Every year, around 300 international undergraduate medical students take the course.